Combining ability and gene action studies in physiological, phenological and yield traits in rice (Oryza sativa L.) - Singh, Ramanjeet; Pandey, Deo Prakash; Kumari, Anjali (Journal of Cereal Research, 2019)
Thirty F1 hybrids from crossing 10 lines and three testers along with their parents were evaluated in RBD with three replications at RWRC, Malan for combining ability and gene action involved in the expression of the traits in rice. Analysis of variance for line Ã— tester mating design with respect to parents, crosses and parents vs. crosses for yield and physiological traits revealed significant differences for almost all the traits studied except total tillers per plant, effective tillers per plant and spikelet fertility in case of parents. Magnitude of Ïƒ2D was found to be higher than that of Ïƒ2A for all the parameters. The average degree of dominance was observed more than one for all the traits. Narrow-sense heritability was obtained low (